Renalase: Another puzzle piece between hypertension and simple renal cysts? - ELÇİOĞLU, ÖMER CELAL; Elcioglu, Omer Celal; AFSAR, Baris; TAKIR, Mumtaz; TOPRAK, Aybala Erek; BAKAN, Ali; BAKAN, Sibel; KOSTEK, Osman; ORAL, Alihan; ERMAN, Hayriye; COVIC, Adrian; Kanbay, Mehmet (My University, 2015)
Since renalase is mostly expressed in kidney tubules, simple renal cyst (SRC) originates from the kidney tubules, and both conditions are related to hypertension, it may be possible that SRC is associated with increased renalase levels. Therefore, in the current study we aimed to confirm the relation between renalase and epinephrine levels, the association between SRC and renalase levels and the association between renalase, blood pressure levels and endothelial dysfunction.